(untitled) (Journal of Additive Manufacturing Technologies, 2023)
With the development of new industries and technological processes, the use of pure materials in sophisticated applications is decreasing due to the demand of conflicting property requirements in single component. The interest on functionally graded ceramics (FGCs) that can be used under severe service conditions with high reliability has increased parallel to demand on complex advanced ceramics in various applications. Conventional methods are not totally capable of cost-effective fabrication of near-net shape FGCs with flexible and complex gradient designs. Lithography-based ceramic manufacturing (LCM) is an additive manufacturing (AM) method that works according to the principle of selective curing of photosensitive formulation according to the digital light processing (DLP) concept. The recently developed LCM multi-material printer allows fabrication of ceramic-ceramic and metal-ceramic combinations with high dimensional precision. Printing methodologies were developed to manufacture FGCs that show both discrete and continuous porosity gradient in parallel and perpendicular to deposition direction. FGC combinations were produced by developing suitable suspensions, optimizing the debinding and sintering processes according to the single material thermo-elastic properties, design, and optimization of printing processes. The main challenges and possible future possibilities in realization of FGCs by LCM will be presented.